PENDAMPINGAN PASCA PANEN KOPI UMKM ULY LASINGAN DESA SANTONG LOMBOK UTARA - Hadi, Sirojul; Apriani, Apriani; Prima Arzani, Lalu Danu; Eka Martiningsih, Ni Gst.Ag. Gde; Arnawa, I Ketut; Suryana, I Made (LPPM Universitas Bina Bangsa, 2025)
Uly Lasingan UMKM faces problems in terms of production and marketing. In terms of production, the problem faced is the lack of drying space and storage for coffee beans. Traditional drying that relies on sunlight causes a long drying time, so the partner's production capacity is highly dependent on the coffee drying process by each farmer which takes 14-20 days. Currently, partners are able to produce up to 600 kg per month, with a breakdown of 300 kg for their own products and 300 kg for roasting services. Every time they produce 300 kg, 240 kg of coffee skin waste is produced which has not been utilized and is only thrown away, even though this waste has the potential to provide added value to UMKM if processed. This production is still relatively small because partners do not have coffee bean storage facilities, so coffee beans are only purchased before the production process, which reduces production effectiveness. Previously, partners had also produced banana sale with a capacity of 2 kg per day, but this activity was stopped due to an earthquake. Meanwhile, in terms of marketing, the problem faced by Uly Lasingan UMKM is the absence of adequate financial records or bookkeeping so that the UMKM will find it difficult to measure business performance and manage cash flow. The purpose of the community service activity is to improve the quality and sales value of post-harvest coffee, increase the knowledge and skills of partners in implementing effective marketing strategies, financial records and effective and efficient organizational management. The method used is five stages of activity, namely socialization, training, technology application, technical assistance and evaluation and program sustainability. The results of this community service activity are the existence of a drying room based on PLTS and IoT, an increase in the amount of raw coffee materials from independent drying by partners, an oil draining machine to revive the banana sale business, procurement of a financial management system and website-based promotion, increasing knowledge and skills about post-harvest handling of coffee through pretests and posttests. The pre-test and post-test results also showed an increase in the level of knowledge of partners from the level of not knowing by 67.19% down to 0.00% and the level of knowing increased from 5.73% to 36.84% and the level of knowing very much increased from 0.52% to 2.11%. This change in the level of knowledge was also reflected in the responses of participants during the training session.